PENGARUH USER EXPERIENCE TERHADAP BEHAVIOR INTENTION TO USE DIGITAL MUSIC STREAMING SERVICES DENGAN ATTITUDE TOWARD BEHAVIOR SEBAGAI MEDIA INTERVENING - Stephanie Raharjo (Jurnal Strategi Pemasaran, 2017)
Technology already changed people behavior incuding the way of enjoying music. Digital Music Streaming Services is one of the option to enjoy music everywhere. Users are able to enjoy music according to their preference (exp : genre and mood). There are so many Digital Music Streaming Services, but this research chose JOOX, Spotify and iTunes as the object due to the increase number of user in Indonesia. That phenomenon also supported by the higher number of smartphone users that always increase each years which approximately reach 62,69 millions users in 2017 (Statista, 2017). This study also chose Kota Surabaya which is the second largest city in Indonesia with the higher internet users which reached 32% of the total population (Kominfo, 2013) as a sample. This research want to analyse the influence of experience toward the perceived of the technology that create behavior intention to use the technology. The data were collected through questionnere used Likert scale (1-5) which distribute in Surabaya and analysed with Smart-PLS.